Evaluation of Binding and Abrasion Properties of Grey Mangrove (Avicennia marina) Leaf Extract Against Escherichia coli K12 DNA - Tudu, Praveen; Mahanty, Shouvik; Sriramulu, Sushmitha; Chaudhuri, Punarbasu; Pathak, Surajit (Anti-Infective Agents, 2021)
Background: Mangroves are globally known for their ecological importance and are found to be extensively used in traditional medicine. Avicennia marina, commonly known as grey mangroves, exhibit strong antimicrobial properties and are also considered to be a promising drug candidate in neutralizing pathogens. Objective: In our present study, the leaf extract from Avicennia marina was isolated using organic solvents of ascensive polarity to evaluate binding and abrasive properties in Escherichia coli K12 DNA. Methods: Samples of the pulverized leaves were used for sequential extraction using ethyl acetate, chloroform and acetone. The minimum inhibitory concentration of isolates from ethyl acetate, chloroform, and acetone were quantified to be 0.125 gL-1, 0.0625 gL-1, and 0.125 gL-1, respectively. These values were further utilized to calculate the binding constant between Escherichia coli DNA and isolates. In addition, the mutagenicity of the isolates was assessed using Ames test in which the Escherichia coli K12 (strain AB1157) bacteria was cultured in minimal glucose media supplemented with isolates for assessing their DNA modifying ability. Further, DNA abrasion potential was assessed for all the isolates using Comet assay. Results: Results of Ames test showed that the isolates have DNA modifying ability, whereas the Comet assay demonstrated that isolates have not exhibited DNA degrading potential. Conclusion: In conclusion, the mechanism by which the isolates degrade the bacterial cell must be contrary to its DNA degrading potential. Experiments paved the way for further quantification and examination using bioinformatics tools to find the best drug candidate and run clinical trials.
Keywords: antibacterial